Role of prolyl hydroxylase domain proteins in bone metabolism - David Wolf; Aruljothi Muralidharan; Subburaman Mohan (Osteoporosis and Sarcopenia, 2022)
Cellular metabolism requires dissolved oxygen gas. Because evolutionary refinements have constrained mammalian dissolved oxygen levels, intracellular oxygen sensors are vital for optimizing the bioenergetic and biosynthetic use of dissolved oxygen. Prolyl hydroxylase domain (PHD) homologs 1–3 (PHD1/2/3) are molecular oxygen dependent non-heme dioxygenases whose enzymatic activity is regulated by the concentration of dissolved oxygen. PHD oxygen dependency has evolved into an important intracellular oxygen sensor. The most well studied mechanism of PHD oxygen-sensing is its regulation of the hypoxia-inducible factor (HIF) hypoxia signaling pathway. Heterodimeric HIF transcription factor activity is regulated post-translationally by selective PHD proline hydroxylation of its HIF1α subunit, accelerating HIF1α ubiquitination and proteasomal degradation, preventing HIF heterodimer assembly, nuclear accumulation, and activation of its target oxygen homeostasis genes. Phd2 has been shown to be the key isoform responsible for HIF1α subunit regulation in many cell types and accordingly disruption of the Phd2 gene results in embryonic lethality. In bone cells Phd2 is expressed in high abundance and tightly regulated. Conditional disruption of the Phd1, Phd2 and/or Phd3 gene in various bone cell types using different Cre drivers reveals a major role for PHD2 in skeletal growth and development. In this review, we will summarize the state of current knowledge on the role and mechanism of action of PHD2 as oxygen sensor in regulating bone metabolism.